Bone transport with an external fixator and a locking plate for segmental tibial defects - C. W. Oh (2018)
Although gradual bone transport may permit the restoration of large-diameter bones, complications are common owing to the long duration of external fixation. In order to reduce such complications, a new technique of bone transport involving the use of an external fixator and a locking plate was devised for segmental tibial bone defects. A total of ten patients (nine men, one woman) with a mean age at operation of 40.4 years (16 to 64) underwent distraction osteogenesis with a locking plate to treat previously infected post-traumatic segmental tibial defects. The locking plate was fixed percutaneously to bridge proximal and distal segments, and was followed by external fixation. After docking, percutaneous screws were fixed at the transported segment through plate holes. At the same time, bone grafting was performed at the docking site with the external fixator removed. The mean defect size was 5.9 cm (3.8 to 9.3) and mean external fixation index was 13.4 days/cm (11.8 to 19.5). In all cases, primary union of the docking site and distraction callus was achieved, with an excellent bony result. There was no recurrence of deep infection or osteomyelitis, and with the exception of one patient with a pre-existing peroneal nerve injury, all achieved an excellent or good functional result. With short external fixation times and low complication rates, bone transport with a locking plate could be recommended for patients with segmental tibial defects. ©2013 The British Editorial Society of Bone & Joint Surgery.